Better Health Choices: Feasability and preliminary effectiveness of a peer delivered healthy lifestyle intervention in a community mental health setting. (April 2020) - Kelly, Peter J.; Baker, Amanda L.; Fagan, Naomi L.; Turner, Alyna; Deane, Frank; McKetin, Rebecca; Callister, Robin; Collins, Clare; Ingram, Isabella; Wolstencroft, Keren; Townsend, Camilla; Osborne, Briony A.; et al.
Highlights: Improving the health behaviors of people living with severe mental illness is a priority. Peer workers are capable of delivering healthy lifestyle interventions. Participants report high rates of satisfaction with peer delivered healthy lifestyle interventions. Abstract: Background: To reduce smoking and improve other health behaviours of people living with severe mental illness, healthy lifestyle interventions have been recommended. One approach to improving the availability of these types of interventions is to utilise the mental health peer workforce. The current study aimed to evaluate the feasibility of peer-workers facilitating a telephone delivered healthy lifestyle intervention within community based mental health settings. The study also examined preliminary outcomes of the intervention. Methods: The study was conducted as a randomised controlled feasibility trial. In addition to treatment as usual, participants randomised to the Treatment Condition were offered BHC. This was an 8-session telephone delivered coaching intervention that encouraged participants to decrease their smoking, increase their intake of fruit and vegetables, and reduce their leisure screen time. Participants in the waitlist Control Condition continued to complete treatment as usual. All participants were engaged with Neami National, an Australian community mental health organisation. Peer-workers were also current employees of Neami National. Results: Forty-three participants were recruited. The average number of sessions completed by participants in the Treatment Condition was 5.7 ( SD  = 2.6; out of 8-sessions). Seventeen participants (77%) completed at least half of the sessions, and nine participants (40%) completed all eight sessions. Participant satisfaction was high, with all participants followed up rating the quality of the service they received as 'good' or 'excellent'. When compared to the Control Condition, people in the Treatment Condition demonstrated greater treatment effects on smoking and leisure screen time. There was only a negligible effect on servings of fruit and vegetable. Conclusions: Results were promising regarding the feasibility of peer-workers delivering BHC. Good retention rates and high consumer satisfaction ratings in the Treatment Condition demonstrated that peer-workers were capable of delivering the intervention to the extent that consumers found it beneficial. The current results suggest that a sufficiently powered, peer delivered randomised controlled trial of BHC is warranted. Study registration: Australian New Zealand Clinical Trials Registry (ANZCTR; Trial ID ACTRN123615000564550).